PARÍS 1808 - De Diego, Rosa (Anales de Filología Francesa, 2008)
This article analyses the changes occurred in Paris in 1808 after the Revolution. Some urban transitions such as “the passages” are studied. Also new spectacles like “Panoramas” are analysed as well as the new habits and activities that began to be in fashion in Paris that became the capital of modernity in the XIXth century.